THE PORTRAYAL OF BLINDNESS IN SHORT STORIES - Agung Wiranata Kusuma (PARADIGM: Journal of Language and Literary Studies, 2021)
Short stories as part of the literature play a significant role in portraying the human lifestyle, including the image of disabilities. Studying the portrayal of disabled people in literature becomes significant to consider the need to change the illustration of disabilities in fiction. There are four short stories selected in this study, namely “Cathedral” By Raymond Carver, “The Blind Man” by Guy de Maupassant, “The Blind Man” by Kate Chopin and “A Man Who Had No Eyes” by Benjamin MacKinlay Kantor. Applying disability theory proposed by Tobin Siebers, this textual analysis study found that the characters in the four stories are portrayed as weak, dependent, unproductive, and other negative prejudice. They receive this treatment due to the social misconception about disabilities.